Galacturonosyltransferase 4 silencing alters pectin composition and carbon partitioning in tomato - de Godoy, Fabiana (2013)
Pectin is a main component of cell wall and the most complex family of polysaccharides in nature. Its composition is essential for the normal growth and morphology pattern, as demonstrated by pectin-defective mutant phenotypes. Besides this basic role in plant physiology, in tomato, pectin structure contributes to very important quality traits such as fruit firmness. Sixty seven different enzymatic activities have been sugested to be required for pectin biosynthesis but only a few genes have been identified and studied so far. In this work we characterized the tomato galacturonosyltransferase family and performed a detailed functional study of the GAUT4 gene. The tomato genome harbors all orthologous genes to those previously described in A. thaliana and a transcriptional profile revealed that the GAUT4 gene is expressed at higher levels in developing organs. GAUT4 silenced tomato plants exhibited an increment in vegetative biomass associated with the palisade parenchyma enlargement. Silenced fruits showed an altered pectin composition, accumulated less starch along with reduced amount of pectin that coincided with an increase in firmness. Moreover, harvest index was dramatically reduced as a consequence of reduction in the fruit weight and number. Altogether, these results suggest that, beyond its role in pectin biosynthesis, GAUT4 interferes with carbon metabolism, partitioning and allocation. Hence, this cell wall-related gene seems to be key in determining plant growth and fruit production in tomato.